Academic self-organization and its relation of Damascus University students (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The aim of the current research is to explore the relationship between academic self-regulation and  in a sample of students of the Faculty of Civil Engineering and the Faculty of Education at Damascus University, in addition to knowledge of the differences in both academic self-regulation and due to specialization and sex (males and females). The sample consisted of (115) male and female students with 62 students from the Faculty of Education and (53) males from the Faculty of Civil Engineering. The number of male and female students was( 59 females and 56 students. .For this purpose, the measure of academic self-regulation was used, after verifying their sincerity and persistence with the sample members of the current study. The results showed that the effect of both specialization and gender had a significant impact on academic self-regulation